Risk-Based Contingency Cost Analysis Using the Expected Monetary Value Method - Ni Luh Ayu Ariati; Dewa Ketut Sudarsana; G.A.P. Candra Dharmayanti (International Journal Labs, 2026)
Construction projects are characterized by high levels of uncertainty that may affect project cost, quality, and schedule performance. Effective risk management is therefore essential to determine contingency costs that adequately reflect project risks. This study aims to identify dominant construction work packages based on risk exposure and estimate risk-based contingency costs for the Main Building Construction Project of the Gianyar Regency Government Center. Project risks were identified through a literature review and Work Breakdown Structure (WBS), validated by experts, and compiled into a risk register. The Probability Impact Matrix (PIM) was used to identify dominant risks, while the Expected Monetary Value (EMV) method was applied to estimate contingency costs for cost (EMVc), quality (EMVq), and schedule (EMVt) aspects. These three aspects were then integrated to determine the overall contingency cost. The results identified ten high-risk work packages, including concrete, reinforcement, steel roof trusses, masonry, sanitary, signage, roof covering, plumbing, road, and softscape works. The EMV analysis produced contingency values of 6.22% (EMVc), 5.95% (EMVq), and 0.70% (EMVt), resulting in an integrated contingency cost of IDR 28.92 billion, equivalent to 12.87% of the project contract value. The findings indicate that contingency cost requirements are primarily influenced by cost and quality risks, providing a more objective basis for contingency reserve allocation during project execution.